An algebraic approach to translating Japanese - Boboc, Valentin (Journal of Language Modelling, 2023)
We use Lambek’s pregroups and the framework of compositional distributional models of language (“DisCoCat”) to study translations from Japanese to English as pairs of functors. Adding decorations to pregroups, we show how to handle word order changes between languages.